2012
DOI: 10.3233/cbm-2012-0233
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutation analysis of EGFR, KRAS, BRAF and PIK3CA in 861 patients with non-small cell lung cancer

Abstract: The prevalence of EGFR, KRAS, BRAF and PIK3CA somatic mutations in 861 randomly selected Chinese patients with non-small cell lung cancer (NSCLC) was assayed by the SurPlex®-xTAG70plex platform and analyzed. The results showed that the occurrence rates were 41.0, 8.0, 0.7 and 3.7%, respectively. The mutation rates significantly correlated with gender, histology and smoking history. The EGFR exon 19, 20 and 21 mutations were higher in females compared to males (p< 0.001, exon 19 and 21; p=0.018, exon 20), highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 34 publications
7
28
0
Order By: Relevance
“…KRAS mutations were identified in 83 (6.7%) patients, consistent with a previous report (24 smokers, and the elderly, which was also found in the present study. No significant association between KRAS mutations and the presence of GGO/GGN was found, as previously reported (25).…”
Section: Discussionsupporting
confidence: 93%
“…KRAS mutations were identified in 83 (6.7%) patients, consistent with a previous report (24 smokers, and the elderly, which was also found in the present study. No significant association between KRAS mutations and the presence of GGO/GGN was found, as previously reported (25).…”
Section: Discussionsupporting
confidence: 93%
“…However, there is also evidence that KRAS mutations, which are more prevalent in males, smokers and invasive mucinous ADCs [15,35,38] (fig. 2), are not an a priori negative factor for TKI administration [39].…”
Section: Discussionmentioning
confidence: 99%
“…28 Mutations in PIK3CA are reported in 4% to 5% of NSCLC patients. 15,16,25 Recently, it was shown that the occurrence of PIK3CA mutations in EGFR mutation-positive tumors increases acquired resistance to EGFR-TKIs. 29 However, further research is required to determine the extent to which these mutations may affect treatment.…”
mentioning
confidence: 99%
“…[12][13][14] Mutations in KRAS and other downstream effectors of the EGFR-pathway, such as BRAF and PIK3CA, have also been identified in NSCLC patients. 15,16 KRAS gene mutations are associated with resistance to EGFR-TKIs and occur in 8% to 16% of NSCLCs, which are increased in patients with adenocarcinomas, men, and smokers. 15,[17][18][19][20][21][22] Mutations in BRAF, which are reported in 0% to 3% of NSCLC patients, 15,[23][24][25] predict a clinical response to EGFR-TKIs.…”
mentioning
confidence: 99%
See 1 more Smart Citation